Effects of restricted suckling on abnormal behaviour, feed intake and weight gain in dairy calves, and udder health and milk let-down in dairy cows - Gratte, Emma (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
The purpose of this study was to increase our knowledge of how to raise healthy calves with no or few abnormal behaviours and favourable weight gain, along with cows with high milk yield and good udder health. The study investigated the effects of restricted suckling versus artificial milk feeding.